Bromic acid-thiourea synergistic leaching of sulfide gold ore - Qiang Zhang; Jing-Ze Duan; Peng-Zhi Xiang (Green Processing and Synthesis)
Bromate–thiourea coordinated leaching of gold sulfide ore for gold sulfide ore as leaching object. The effects of leaching reagent, stirring speed, and leaching time on gold leaching were investigated in this article. The results showed that the optimum leaching conditions were potassium bromate 0.1 M, thiourea 0.6 g·L−1, hydrochloric acid 0.2 M, agitation speed 250 rpm, ratio of liquid to solid 4, and leaching time 10 min. Under these conditions, high efficiency and rapid leaching of gold can be achieved, and reagent consumption is reduced. The research results have theoretical and practical significance for expanding new green gold extraction technology.